Smoking status and psychosocial factors in binge eating disorder and bulimia nervosa. (April 2016) - Chao, Ariana M.; White, Marney A.; Grilo, Carlos M.
Abstract: Objective: To examine eating-disorder psychopathology and depressive symptoms by smoking status (never, former, or current smoker) in persons with binge eating disorder (BED) and bulimia nervosa (BN). Methods: Participants were 575 adult volunteers from the community (mean age = 36.0 ± 12 years and BMI = 32.9 ± 9.5 kg/m 2 ; 80% white; 88% female) who were classified with BED (n = 410) or BN (n = 165). Participants completed a battery of questionnaires, including items about current and historical cigarette smoking, the Eating Disorder Examination —Questionnaire, and the Beck Depression Inventory. Results: Among those with BED, depressive symptoms were significantly higher in current smokers than former or never smokers ( p  = .001). There were no significant differences in depressive symptoms by smoking status in participants with BN and no differences in eating-disorder psychopathology by smoking status in either the BED or BN groups. Discussion: In this non-clinical group of community volunteers, we found that smoking history or status was not associated with eating disorder psychopathology in participants classified with BED and BN but was significantly associated with depressive symptoms in participants with BED. Highlights: We examined eating disorder psychopathology and depressive symptoms by smoking status in BED and BN. Among those with BED, depressive symptoms were higher in current smokers. No differences in depressive symptoms by smoking status in BN. No differences in eating disorder psychopathology by smoking status in BED or BN.